Temporal Distribution Of Arthropods In Heliotropium indicum In Jombang District As E-Catalog Development - Yesika Febriani; Anggun Wulandari; Devita Sari (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2021)
Arthropods have an important role in the rice field ecosystem, namely as natural enemies (predators, parasitoids, and control pathogens) that can be used as pest control efforts. The diversity of natural enemies can be seen from his visits to the flowering plant (refugia) namely Heliotropium indicum in Jombang Regency by looking at the temporal distribution of each observation. The purpose of this study was to determine the distribution of daily temporal visits of arthropods on Heliotropium indicum in Ploso and Plandaan sub-districts and to be used as material for developing e-catalogs. This research was conducted in February 2021 using the visual control method by observing 3 replicates at 06.00-07.00 am, 11.00-12.00 noon, and 16.00-17.00 pm, the data obtained were analyzed descriptively by calculating the average frequency each time. observations (hours). The results of the study on the temporal distribution of arthropods on the Heliotropium indicum plant can be found that certain arthropods are often found at certain hours, namely, the arthropods that are active in the morning and evening are the Pentatomidae and Muscidae families, the arthropod families that are active during the day are Mantidae and the arthropod families that are active throughout the day are Formicidae, Acrididae, and Coccinellidae. The results of the research were developed into learning media in the form of an e-catalog. The developed e-catalog contains images of arthropods visiting the Heliotropium indicum plant, their classification, and a description of their morphology.